The Role of Plant-Derived Natural Products as a Regulator of the Tyrosine Kinase Pathway in the Management of Lung Cancer - Faris Alrumaihi; Arshad Husain Rahmani; Sitrarasu Vijaya Prabhu; Vikalp Kumar; Shehwaz Anwar (Current Issues in Molecular Biology, 2025)
One of the most common malignant tumors worldwide is lung cancer, and it is associated with the highest death rate among all cancers. Traditional treatment options for lung cancer include radiation, chemotherapy, targeted therapy, and surgical resection. However, the survival rate is low, and the outlook is still dreadfully dire. The pursuit of a paradigm change in treatment approaches is, therefore, imperative. Tyrosine kinases (TKs), a subclass of protein kinases, regulate vital cellular function by phosphorylating tyrosine residues in proteins. Mutations, overexpression, and autocrine paracrine stimulation can transform TKs into oncogenic drivers, causing cancer pathogenesis. Tyrosine kinase inhibitors (TKIs) have emerged as an attractive targeted therapy option, especially for non-small cell lung cancer (NSCLC). However, resistance to TKIs, and adverse cardiovascular effects such as heart failure, atrial fibrillation, hypertension, and sudden death, are among the most common adverse effects of TKIs. There is increasing interest in plant-derived natural products in the hunt for powerful chemosensitizer and pathway modulators for enhancing TKI activity and/or overcoming resistance mechanisms. This highlights the mechanism of TKs’ activation in cancer, the role of TKIs in NSCLC mechanisms, and the challenges posed by TKI-acquired resistance. Additionally, we explored various plant-derived natural products’ bioactive compounds with the chemosensitizer and pathway-modulating potential with TKs’ inhibitory and anticancer effects. Our review suggests that a combination of natural products with TKIs may provide a novel and promising strategy for overcoming resistance in lung cancer. In future, further preclinical and clinical studies are advised.